Reduction in the mutagenicity of synthetic dyes by successive treatment with activated sludge and the ligninolytic fungus, Irpex lacteus - Malachová, Katerina; Pavlícková, Zuzana; Novotný, Cenek; Svobodová, Katerina; Lednická, Denisa; Musílková, Eva (Environmental and molecular mutagenesis, 2006)
Synthetic dyes are released in wastewater from textile manufacturing plants, and many of these dyes are genotoxic. In the present study, the mutagenicity of azo, anthraquinone, and triphenyl methane dyes was investigated before and after successive biodegradation with activated sludge and the ligninolytic fungus, Irpex lacteus. Two biodegradation systems were used to reduce the genotoxicity of dyes that were not efficiently inactivated by activated sludge alone. Mutagenicity was monitored with the Salmonella reversion assay conducted with the base-pair substitution detector strains, TA100 and YG1042, and the frame-shift detector strains, TA98 and YG1041, with and without rat liver S9. All dyes except for Congo Red (CR) were mutagenic with S9 activation. Assays conducted with the dyes indicated that only the azo dye Reactive Orange 16 (RO16) was mutagenic in both TA98 and TA100. Methyl Red and Disperse Blue 3 (DB3) were mutagenic in TA98, YG1041 and YG1042, while Reactive Black 5 was mutagenic in YG1041 and YG1042. Remazol Brilliant Blue R (RBBR), Crystal violet (CV) and Bromophenol Blue (BPB) were mutagenic only in TA98, but the toxicity of the latter two dyes complicated the evaluation of their mutagenicity. CR was not mutagenic in any of the tester strains. Biodegradation studies conducted with RO16 and DB3 indicated that the two-step biodegradation process reduced the mutagenic potential of RO16 and DB3 to a greater extent than activated sludge alone; the mutagenicity of the two dyes was reduced by 95.2% and 77.8%, respectively, by the two-step process. These data indicate that the combined biodegradation process may be useful for reducing the mutagenicity associated with wastewater from textile factories that contain recalcitrant dyes.
Keywords: Basidiomycota; Coloring Agents; chemické látky znečišťující vodu; Biodegradation, Environmental; čištění vody; Mutagenicity Tests; Water Purification; molekulární struktura; Textile Industry; Molecular Structure; Water Pollutants, Chemical; textilní průmysl; Mutagens; mutageny; barvicí látky; Salmonella typhimurium; odpadní vody; Sewage; biodegradace; testy genotoxicity